Looking for Alaska - Green, John. (Hudson St., New York : Speak, 2005)
Sixteen-year-old Miles' first year at Culver Creek Preparatory School in Alabama includes good friends and great pranks, but is defined by the search for answers about life and death after a fatal car crash.
Keywords: Boarding schools -- Juvenile fiction; Boarding schools -- Alabama -- Juvenile fiction; Death -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Schools -- Juvenile fiction